Current challenges for the targeted delivery and molecular imaging of stem cells in animal models. Issue 4 (4th July 2017) - Momeni, Arezoo; Neelamegham, Sriram; Parashurama, Natesh
ABSTRACT: In contrast to conventional, molecular medicine that focuses on targeting specific pathways, stem cell therapy aims to perturb many related mechanisms in order to derive therapeutic benefit. This emerging modality is inherently complex due to the variety of cell types that can be used, delivery approaches that need to be optimized in order to target the cellular therapeutic to specific sites in vivo, and non-invasive imaging methods that are needed to monitor cell fate. This review highlights advancements in the field, with focus on recent publications that use preclinical animal models for cardiovascular stem cell therapy. It highlights studies where cell adhesion engineering (CAE) has been used to functionalize stem cells to home them to sites of therapy, much like peripheral blood neutrophils. It also describes the current state of molecular imaging approaches that aim to non-invasively track the spatio-temporal pattern of stem cell delivery in living subjects.